Saudi Arabia : Reports on the Observance of Standards and Codes. (IMF Staff Country Reports; Country Report, 2012)
Saudi Arabia's Report on Standards and Codes has been examined. The Capital Market Authority (CMA) has made significant progress in establishing its supervision credentials, including issuing implementing regulations. The CMA approach to supervision is both risk-based and compliance-focused, and the cost of compliance needs to be a more central focus when establishing mandatory obligations. The CMA has general and broad powers for inspection and investigation, and it conducts full electronic surveillance of the market. The CMA has the authority to investigate potential violations and to bring enforcement action seeking civil and criminal penalties.